Peculiarities of the professional dialogue mediated by modern means of telecommunication in the process of training future specialists in economics - Kramarenko, Tetiana; Крамаренко, Тетяна Володимирівна (Університет імені Альфреда Нобеля, 2021)
The article considers and analyzes the features of professional dialogue mediated by means of information and communication technologies in the training of future economic specialists, the main aspects of the use of mediated dialogue in foreign language teaching. Possibilities of communication mediated by information and communication technologies in the process of learning a foreign language by future specialists in economics are considered. The concept of indirect dialogue based on the analysis of existing approaches of scientists to the problem of using information and communication technologies in the process of training future specialists in economics is revealed. Features of dialogue on the basis of Internet technologies are considered. The classification of types of educational dialogue by means of information technologies on pedagogical orientation is given. The issues of culture and ethics of behavior in the information space during the dialogue mediated by modern means of telecommunications, the use of information presented in information networks are substantiated. Based on the analysis of various approaches to the use of computer communication, the essence of this concept is revealed and the ways of its further use in the training of economics specialists are substantiated. The requirements for professional dialogue mediated by computer means are presented. The system of conditions that promote the implementation of intersubject dialogue, taking into account the specifics of its organization in the computer environment, ie: providing internal and external dialogue of the student; psychological comfort of students in dialogic interaction; depth of dialogue; compliance of the purpose of the dialogue with the motive of the student’s entry into it; dialogic content of educational material; readiness of the learning situation and its participants for dialogue; the expediency of including in the educational process of computer-mediated dialogue; attitude to the computer as a quasi-subject of dialogue. It was found that it is advisable to combine modern information and communication technologies with traditional learning technologies in the learning process. It is proved that the electronic environment creates conditions for autonomous, individual-cooperative, joint activity of students, promoting the formation of a culture of professional dialogue, personal, communicative self-development, and the use of information and communication technologies opens new prospects for professional training of future economists. У статті розглянуто та проаналізовано особливості професійного діалогу, опосередкованого засобами інформаційно-комунікаційних технологій, у підготовці майбутніх економічних спеціалістів, основні аспекти використання опосередкованого діалогу у навчанні іноземної мови. Розглянуто можливості комунікації, опосередкованої інформаційно-комунікаційними технологіями, у процесі вивчення іноземної мови майбутніми економістами. Розкрито концепцію непрямого діалогу на основі аналізу існуючих підходів вчених до проблеми використання інформаційно-комунікаційних технологій у процесі підготовки майбутніх економічних спеціалістів. Розглянуто особливості діалогу на основі Інтернет-технологій. Подано класифікацію видів навчального діалогу засобами інформаційних технологій за педагогічною спрямованістю. Обґрунтовано питання культури та етики поведінки в інформаційному просторі під час діалогу, опосередкованого сучасними засобами телекомунікацій, використання інформації, представленої в інформаційних мережах. На основі аналізу різноманітних підходів до використання комп’ютерного зв’язку розкрито сутність цього поняття та обґрунтовано шляхи його подальшого використання у підготовці фахівців економіки. Представлено вимоги до професійного діалогу, опосередкованого комп’ютерними засобами. Система умов, що сприяють здійсненню міжпредметного діалогу з урахуванням специфіки його організації в комп’ютерному середовищі, тобто: забезпечення внутрішнього та зовнішнього діалогу студента; психологічний комфорт учнів у діалогічній взаємодії; глибина діалогу; відповідність мети діалогу мотиву вступу в нього учня; діалогічний зміст навчального матеріалу; готовність навчальної ситуації та її учасників до діалогу; доцільність включення до навчального процесу комп’ютерно-опосередкованого діалогу; ставлення до комп’ютера як до квазісуб’єкта діалогу. Виявлено, що в процесі навчання доцільно поєднувати сучасні інформаційно-комунікаційні технології з традиційними технологіями навчання. Доведено, що електронне середовище створює умови для автономної, індивідуально-кооперативної, спільної діяльності студентів, сприяючи формуванню культури професійного діалогу, особистісному, комунікативному саморозвитку, а використання інформаційно-комунікаційних технологій відкриває нові перспективи для професійна підготовка майбутніх економістів
Особливості професійного діалогу, опосередкованого сучасними засобами телекомунікації в процесі підготовки майбутніх фахівців економіки
Keywords: professional dialogue; професійний діалог; indirect dialogue; опосередкований діалог; future specialists; майбутні фахівці; etiquette; етикет; culture of dialogue; культура діалогу; information and communication technologies; інформаційно-комунікаційні технології; educational dialogue; навчальний діалог; communication in a computer environment; комунікація у комп’ютерному середовищі; joint activities; спільна діяльність; rules of subordination; правила субординації